[(Ni-Ni-Ni)@(Ge9)2]4-: a linear triatomic nickel filament enclosed in a dimer of nine-atom germanium clusters. - Goicoechea, J; Sevov, S (2005)
(Figure Presented) Under wraps: A linear nickel filament is "wrapped" inside an eighteen-atom germanium enclosure made of two nine-atom deltahedral clusters (see structure; green Ge, yellow Ni). © 2005 Wiley-VCH Verlag GmbH and Co. KGaA.